Addressing Digital Addiction Among University Students: A Study of Digital Detox Techniques in Smartphone and Social Media Addiction - Deniz Yaramış; Recep Ünal (Yeni Medya, 2024)
While new media offers opportunities that simplify our lives, it also poses the risk of making us dependent on digital technologies. Problematic use of digital technologies can lead to digital addiction, which in turn can result in physical, mental, and social problems. The primary research problem of this study is to understand university students’ awareness of and practical use of digital detox methods that they can implement on their own within the context of digital addiction. Additionally, the study aims to determine whether young people perceive personal methods like digital detox as a viable solution to this significant issue. Additionally, digital detox methods that individuals can implement based on their own willpower and resources were explored. In this study, which employed both quantitative and qualitative research techniques, the addiction levels of 141 out of 240 undergraduate students enrolled in the Radio, Television, and Cinema Department of Mersin University’s Faculty of Communication for the 2021-2022 spring semester were measured through an online survey. In the second stage, focus group interviews were conducted with 23 students, categorized into three separate groups based on their addiction levels, to discuss their views on both digital addiction and digital detox practices. The interviews revealed that a majority of the students experienced withdrawal symptoms, indicative of digital addiction, and manifested this in their behavior.